Question

solve differential equation ((x)2 - xy +(y)2)dx - xydy = 0

solve differential equation (x^2-xy+y^2)dx - xydy = 0

Answer #1

Solve the Homogeneous differential equation
(7 y^2 + 1 xy)dx - 1 x^2 dy = 0
(a) A one-parameter family of solution of the equation is y(x)
=
(b) The particular solution of the equation subject to the
initial condition y(1) =1/7.

(x-y)dx + (y+x)dy =0 Solve the differential equation

Use the method for solving homogeneous equations to solve the
following differential equation.
(9x^2-y^2)dx+(xy-x^3y^-1)dy=0
solution is F(x,y)=C, Where C= ?

solve the differential equation...
(x2-1)(dy/dx)+xy=0

Solve the following differential equation using taylor series
centered at x=0:
(2+x^2)y''-xy'+4y = 0

Solve the differential equation:
d/dx*y(x) + y(x) = 3
y(x) = ?

Solve the equation.
(2x^3+xy)dx+(x^3y^3-x^2)dy=0
give answer in form F(x,y)=c

Solve the given differential equation
y-x(dy/dx)=3-2x2(dy/dx)

A Bernoulli differential equation is one of the form
dy/dx+P(x)y=Q(x)y^n (∗)
Observe that, if n=0 or 1, the Bernoulli equation is linear. For
other values of n, the substitution u=y^(1−n) transforms the
Bernoulli equation into the linear equation
du/dx+(1−n)P(x)u=(1−n)Q(x).
Consider the initial value problem xy′+y=−8xy^2, y(1)=−1.
(a) This differential equation can be written in the form (∗)
with P(x)=_____, Q(x)=_____, and n=_____.
(b) The substitution u=_____ will transform it into the linear
equation du/dx+______u=_____.
(c) Using the substitution in part...

Solve the differential equation by using integrating factors.
xy' = 4y − 6x^2
y(x)=?

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 7 minutes ago

asked 10 minutes ago

asked 10 minutes ago

asked 24 minutes ago

asked 28 minutes ago

asked 30 minutes ago

asked 31 minutes ago

asked 31 minutes ago

asked 31 minutes ago

asked 33 minutes ago

asked 46 minutes ago

asked 46 minutes ago